Market Price vs. Economic Indicators of Shareholders’ Value: Empirical Evidences from Indian Corporate Sector - Kumar, Ashok; Pal, Karam (Gyan Management Journal, 2007)
Shareholders’ value is becoming more and more important in the wake of globalization. Measurement of shareholders’ value in an enterprise forms the core of corporate performance. This article examines that how Market Price is correlated with the firm performance in terms of financial measures of the company such as Return on Capital Employed (ROCE), Earning Per Share (EPS), Net Operating Profit after Tax (NOPAT), and purely economic factor of the company such as Capital Productivity (Kp) and Labour Productivity (Lp). A sample of 30 companies (BSE-Sensex) has been taken for the period ranging 1996-97 to 2005-06. The study concludes that Market Price is positively correlated with ROCE, EPS and ARNW on the one hand and negatively correlated with Lp and Kp ?n the other hand.